Evaluation of the eutrophication level of the Cañoncillo lagoon, La Libertad, Peru. (LACCEI, 2024)
The present research was carried out in the Cañoncillo lagoon located in the district of San Pedro de Lloc, Province of Pacasmayo, Department of La Libertad. The objective of the research was to evaluate the eutrophication level of the Cañoncillo lagoon. To achieve this objective, five sampling stations were identified along the water body, where in situ parameters such as pH, temperature, dissolved oxygen, electrical conductivity and water transparency were measured. In addition, two samples were collected from each point at different depths (1 m and 3 m) using a hydrographic bottle. Nitrates and phosphates were analyzed from each sample by the colorimetric method and chlorophyll-a by the trichromatic method. Two indices were then applied to determine the level of eutrophication of the lagoon: the Nutrient Eutrophication Index (EI) of Karydis et al. and the Trophic State Index (TSI) of Carlson, modified by Toledo et al. The results indicated that the pH of the water at 1 m depth presented values between 7.94 and 8.15, and at 3 m between 7.83 and 8.20 the temperature at 1 m depth between 22.1 and 22.8 °C, while at 3 m the data varied between 22.2 and 23. 2 °C dissolved oxygen at 1 m depth presented data between 5.45 and 7.63 mg/L and at 3 m between 3.82 and 8.17 mg/L electrical conductivity at 1 m had values between 393 and 404 µs/cm and at 3 m between 298 and 412 mg/L, nitrate concentration at 1 m depth varied between 0. 39 and 1.40 mg/L and at 3 m between 1.07 and 2.10 mg/L phosphate concentration at 1 m depth ranged between 0.08 and 0.18 mg/L, and at 3 m between 0.13 and 0.20 mg/L chlorophyll-a at 1 m depth presented higher concentrations than at 3 m. On the other hand, from the application of the EI, a value of 2.23 was obtained for nitrates and 0.94 for phosphates while the EIT for transparency was 38.449 and for chlorophyll-a 66.77. Finally, it was concluded that the eutrophication level of the Cañoncillo lagoon was oligotrophic based on nitrates, phosphates and transparency and eutrophic based on chlorophyll-a, thus identifying that the proliferation of aquatic plants is not directly related to the concentration of the nutrients analyzed.